Single early instillation of mitomycin C and urinary alkalinization in low-risk non-muscle-invasive bladder cancer: a preliminary study - Ersoy H; Yaytokgil M; Karakoyunlu AN; Topaloglu H; Sagnak L; Ozok HU (Dove Medical Press, 2012)
Hamit Ersoy, Muhammet Yaytokgil, Ahmet Nihat Karakoyunlu, Hikmet Topaloglu, Levent Sagnak, Hakki Ugur OzokDepartment of Urology, Diskapi Yildirim Beyazit Training and Research Hospital, Ministry of Health, Ankara, TurkeyBackground: The purpose of this study was to determine the effectiveness of a single early instillation of mitomycin C (MMC) after transurethral resection of bladder tumor (TURBT) together with urinary alkalinization in patients with low-risk non-muscle-invasive bladder cancer (NMIBC).Methods: Between February 2006 and November 2010, patients diagnosed as having a primary bladder tumor were randomized into standard and optimized treatment groups. The treatment groups were formed prospectively from patients with NMIBC according to results of pathological examination postoperatively, whereas the control group was formed retrospectively. Patients in the standard group (n = 11) were given intravesical MMC 40 mg in the first 6 hours after TURBT, while the patients in the optimized group (n = 15) underwent urinary alkalinization prior to MMC. In the control group (n = 23), no drug treatment was given. The patients were followed after surgery at months 3 and 12, and then annually for the first 5 years using cystoscopy and ultrasound. Time to recurrence and recurrence-free survival rates were calculated.Results: There were no statistically significant differences between the standard and optimized groups, between the control and optimized groups, or between the control and standard groups in terms of mean recurrence-free survival rates (P = 0.132, 0.645, and 0.173, respectively). The mean time to recurrence was 34.8 (range 28.5–41.1) months in the optimized group and 51.8 (range 44.3–59.2) months in the control group. There was no recurrence during the follow-up period in the standard group.Conclusion: The results of this preliminary study could not demonstrate the efficacy of urinary alkalinization before a single dose of early MMC following TURBT to increase the effectiveness of the MMC, so we did not continue the study further.Keywords: alkalinization, bladder, mitomycin C, tumor